Is Ghana making progress in agro-processing? Evidence from an inventory of processed food products in retail shops in Accra - Andam, Kwaw S.; Al-Hassan, Ramatu M.; Asante, Seth; Diao, Xinshen (International Food Policy Research Institute, 2015)
One likely outcome of Ghana’s rising household incomes and increasing urbanization is a higher demand for processed foods. The question remains whether this expected higher demand will generate opportunities for growth in domestic agro-processing. This study assesses the performance of the agro-processing sector in Ghana through an inventory of processed and packaged food items in retail shops around Accra. The inventory shows: 1. The agro-processing subsector offers opportunities for domestic firms, with Ghanaian brands accounting for 27 percent of the items identified. 2. In addition to forming nearly a third of products identified, locally-processed products have penetrated diverse market segments with sales across a variety of retail outlets. 3. Regional imports of processed and packaged food items are low. Excluding South African brands, which accounted for 7.8 percent of imports, only 4.3 percent of the items were imported from other African countries. 4. Domestic agro-processors provided the highest share of products among processed starches and cereals, while imports dominate processed dairy, fruits, vegetables, and meat products.